BepiColombo Mio Observations of Low‐Energy Ions During the First Mercury Flyby: Initial Results. Issue 17 (8th September 2022) - Harada, Yuki; Aizawa, Sae; Saito, Yoshifumi; André, Nicolas; Persson, Moa; Delcourt, Dominique; Hadid, Lina Z.; Fraenz, Markus; Yokota, Shoichiro; Fedorov, Andréi; Miyake, Wataru; Penou, Emmanuel; et al.
Abstract: We present initial results of low‐energy ion observations from BepiColombo's first Mercury flyby. Unprecedentedly high time resolution measurements of low energy ions at Mercury by BepiColombo Mio reveal rapid (a few seconds) and large (1–2 orders of magnitude) fluctuations of ion flux around the magnetopause and within the magnetosphere. Around the magnetic equator in the pre‐midnight magnetotail, Mio observed plasma sheet ions consistent with previous observations. In the midnight magnetotail near the closest approach, Mio observed the co‐existence of high‐energy (∼keV/q) and low‐energy (<∼300 eV/q) ion components. The low‐energy component is inferred to be cold with a temperature well below 100 eV and have a major contribution to the total density as opposed to previously reported cold tenuous ions. Future observations by Mio will provide insights into the sources, transport, and acceleration of the newly identified ion components. Plain Language Summary: BepiColombo, launched on 20 October 2018, is now en route to Mercury. Along its 7‐year journey to the Mercury orbit insertion, BepiColombo conducted, and will conduct, nine planetary flybys in total. This paper presents brand‐new observations of ions (positively charged particles) in Mercury's magnetosphere by BepiColombo Mio during its first encounter with Mercury. Thanks to high‐time resolution measurements by Mio, it is revealed that ions around Mercury change dramatically and rapidly just over a few seconds. Mio also observed an unexpectedly dense ion population with low energies, for which we do not have a definitive explanation yet. Future flyby and in‐orbit observations by BepiColombo will provide key information for unraveling the dynamics and sources of ions in Mercury's magnetosphere. Key Points: We present initial reports on low energy ion observations during BepiColombo's first Mercury flyby Mio observed large fluctuations of ion flux with time scales down to a few seconds around the magnetopause and within the magnetosphere Ion energy spectra obtained in the midnight magnetotail suggest the presence of an unexpectedly dense cold component